Penatalaksanaan Holistik Penyakit Congestive Heart Failure pada Wanita Lanjut Usia Melalui Pendekatan Kedokteran Keluarga - Muhammad Dimas Pangestu; Azelia Nusadewiarti (Majority, 2020)
From World Health Organization (WHO) in 2016 asserted that in 2015 around 23 million or about 54% people deaths caused of Congestive Heart Failure (CHF). Based on data from the Lampung Provincial Health Office in 2016 with inpatient data on heart failure clients increased with a percentage of 42.6%, mostly in old age occurred 50% (60-70years). Implementation of family doctor services to patients by identifying risk factors, clinical problems, and management with a patient centered approach and family approach. The study conducted was Case Report. Primary data were obtained through history taking and physical examination by making home visits, filling family folders, and filling patient files. The assessment is based on a quantitative and qualitative holistic initial diagnosis, process, and end of visit. Based on a holistic diagnosis, the patient suffers from heart failure with grade II hypertension. Complaints felt by the patient are heartburn, chest palpitations, weakness, dizziness, decreased appetite, and fatigue. Based on social functions, patients have limitations in heavy activities. The intervention was carried out non-medically through education and counseling with a family approach and medically by giving Digoxin, Furosemide, Bisoprolol dan Clopidogrel (CPG). During the visit during the control, the patient's concern about heart disease and hypertension they experienced was reduced and the patient understood the disease. Heart failure accompanied by hypertension occurs mostly in old age. The diagnosis of CHF accompanied by Grade II Hypertension in this case is consistent with the theory and critical review of recent research. There are internal and external risk factors triggering the emergence of CHF. This is stated by several theories which are a source of reference. The role of the family is important in the care and treatment of sick family members.